Effect of Covid-19 on SN Learners’ Access to Training in TVETs - Sirima, Lornah C.Nakera (Machakos University Press, 2021)
Education is vital as it gives students opportunities for growth, development and hope for a brighter future. This is in line with Sustainable Development Goal number four which states that: Quality Education seeks to ensure inclusive and equitable quality education and promoting lifelong learning opportunities for all. During the Covid-19 pandemic schools and higher education institutions closed as directed by the government. The closure put learners with special needs (Especially the visually and Hearing impaired) at more vulnerability thus increasing pre-existing education disparities by reducing the opportunities for many of the most vulnerable children who experience various challenges. Institutions of higher learning including the Technical and Vocational Education Training Institutes (TVETs) replaced face-to-face lectures with online learning during Covid-19 pandemic thus affecting learning and education of those with special needs. Further, closure of schools has other effects on the provision of essential services in education to children with special needs (Visually and Hearing impaired) including access to digital education and students’ sense of belonging to schools; these are important for inclusion in education. This paper centered on access and inclusive education for all which is in line with SDG 4. The paper further examined the schools re-opening issue by giving the World Health Organization Covid-19 guidelines and strategies aimed at ensuring that the pandemic does not hinder inclusion of children with special needs (Visually and Hearing impaired) in education system in case of future lockdowns.
Keywords: Special Needs Learners; Visually Impaired; Hearing Impaired; Covid-19; Access; Inclusion